1991
DOI: 10.1007/bf01319245
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the 3′ terminal region of lettuce mosaic potyvirus RNA shows a Gln/Val dipeptide at the cleavage site between the polymerase and the coat protein

Abstract: DNA complementary to the 3' terminal 1651 nucleotides of the genome of the common strain of lettuce mosaic virus (LMV-O) has been cloned and sequenced. Microsequencing of the N-terminus enabled localization of the coat protein gene in this sequence. It showed also that the LMV coat protein coding region is at the 3' end of the genome, and that the coat protein is processed from a larger protein by cleavage at an unusual Q/V dipeptide between the polymerase and the coat protein. This is the first report of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Conserved amino acids are shown in upper case and identical amino acids are shown in the consensus row. The eight conserved motifs according to Koonin [25] are indicated by Roman numbering [13]); PRSV-W [31]; TEV-NAT [2]; TEV-HAT [1]; PPV-D [34]; turnip mosaic virus (TuMV; [42]); LMoV [27]; OrMV [8]; bean yellow mosaic virus (BYMV-GDD; [21]); clover yellow vein virus (CIYVV)-N [6]; SCMV-MDB and SCMV-SC [18] and T V M V [14] was found for P P V -N A T [28] in comparison to P P V -A T [26]. Inspection of the N-terminus of I S M V -C P reveals a D A A sequence.…”
Section: Ctagtggatcc-(t)io-g/a/t/c-3'mentioning
confidence: 99%
“…Conserved amino acids are shown in upper case and identical amino acids are shown in the consensus row. The eight conserved motifs according to Koonin [25] are indicated by Roman numbering [13]); PRSV-W [31]; TEV-NAT [2]; TEV-HAT [1]; PPV-D [34]; turnip mosaic virus (TuMV; [42]); LMoV [27]; OrMV [8]; bean yellow mosaic virus (BYMV-GDD; [21]); clover yellow vein virus (CIYVV)-N [6]; SCMV-MDB and SCMV-SC [18] and T V M V [14] was found for P P V -N A T [28] in comparison to P P V -A T [26]. Inspection of the N-terminus of I S M V -C P reveals a D A A sequence.…”
Section: Ctagtggatcc-(t)io-g/a/t/c-3'mentioning
confidence: 99%
“…2) predicted cleavage sites in the C-terminal halves of the potyviral polyproteins revealed that the 49K NIa protein cleaves at Q/A, Q/G, Q/S, Q/T, Q/V or Q/E dipeptide sequences, and valine was found in most potyviruses at position P4 of the cleavage sites (Dougherty & Carrington, 1988;Ghabrial eta/., 1990, Dinant et al, 1991Johansen et al, 1991). Based on these rules, five putative cleavage sites recognized by the NIa protein were identified in the PRSV polyprotein (Table 1).…”
Section: Assignment Of Polyprotein Cleavage Sitesmentioning
confidence: 99%
“…Comparison of the determined and predicted cleavage sites in the C-terminal region of the potyvirus polyproteins revealed that the polyproteins were usually cleaved at Q/A, Q/G, Q/S, Q/T, Q/V or Q/E dipeptide sequences by the NIa proteinase and valine was usually found in the P4 position of the cleavage sites I- 11,12,16,19,33]. The coding nucleotide sequence and the sequence of the first 20 amino acids at the N-terminus of TVBMV coat protein enabled us to locate Fig.…”
Section: Resultsmentioning
confidence: 99%